2008
DOI: 10.1021/es070502d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Snow and Ice Crystal Formation and Accumulation on Mercury Deposition to the Arctic

Abstract: Mercury is deposited to the Polar Regions during springtime atmospheric mercury depletion events (AMDEs) but the relationship between snow and ice crystal formation and mercury deposition is not well understood. The objective of this investigation was to determine if mercury concentrations were related to the type and formation of snow and ice crystals. On the basis of almost three hundred analyses of samples collected in the Alaskan Arctic, we suggest that kinetic crystals growing from the vapor phase, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 51 publications
(106 reference statements)
5
138
0
Order By: Relevance
“…[6] The results suggest that at least half of the AMDE Hg is lost within 1 week since deposition but that ,10 to 25 % remains. A recent study based on snow collected on land and on the sea ice near Barrow, Alaska, [5] provides some insight into why the results in Fig. 10 suggest that the variance in Hg concentrations increases with time.…”
Section: Eastern Beaufort Sea Belugamentioning
confidence: 90%
See 1 more Smart Citation
“…[6] The results suggest that at least half of the AMDE Hg is lost within 1 week since deposition but that ,10 to 25 % remains. A recent study based on snow collected on land and on the sea ice near Barrow, Alaska, [5] provides some insight into why the results in Fig. 10 suggest that the variance in Hg concentrations increases with time.…”
Section: Eastern Beaufort Sea Belugamentioning
confidence: 90%
“…When new sea ice (nilas) forms, brine and frost flowers fractionate halogens and other chemical compounds, depositing them onto the sea ice surface. [5][6][7] These sea ice processes, together with the seasonality of sunlight, are key factors underpinning Arctic Mercury Depletion Events (AMDEs), which are unique to polar regions. The most visible change in the Arctic over the past 30 years is the loss of multiyear sea ice from the Arctic Ocean and its replacement by seasonal sea ice.…”
Section: Jane Kirk Is An Environment Canada Research Scientist At Thementioning
confidence: 99%
“…Other aerosols such as sea salts and ice crystals are also common during the spring at Alert. Both these aerosols are effective scavengers of RGM and have been associated with elevated levels of PHg and Hg in the snow (Rutter and Schauer, 2007a;Douglas et al, 2008;Malcolm et al, 2010;Steffen et al, 2013). Coarse particle Na + , mostly sea salt derived, is elevated in February and at the beginning of March at Alert (Leaitch et al, 2014) but decreases in April.…”
Section: Gem (Ng Mmentioning
confidence: 99%
“…Several studies have been reported on the deposition and fate of mercury on snow and ice surfaces (Boutron et al, 1998; Lu et al Lalonde et al, 2002;Dommergue et al, 2003aDommergue et al, , b, 2009Ariya et al, 2004;Douglas and Sturm, 2004;Ferrari et al, 2004aFerrari et al, , b, 2005Douglas et al, 2005Douglas et al, , 2008Douglas et al, , 2012Fitzgerald et al, 2005;Lahoutifard et al, 2005;St. Louis et al, 2005;Kirk et al, 2006;Constant et al, 2007;Poulain et al, 2007;Outridge et al, 2008;Poissant et al, 2008;Carignan and Sonke, 2010;Durnford and Dastoor, 2011;Durnford et al, 2012), but the long-term snow data presented here are unique.…”
Section: Mercury In Snow At Alertmentioning
confidence: 99%
“…Instead, Asuma et al [40] observed both densely rimed dendrites and graupels in the western Canadian Arctic together with crystals grown by diffusion (plates, columns, bullet rosettes). These two different growth [41] collected snow and ice crystals in the air, on the ground and on sea-ice in Alaska to study the deposition of mercury, predominantly present in the atmosphere as a gaseous element. Their results showed that mercury concentrations were related to the type and formation of snow and ice crystals.…”
Section: Physical and Chemical Processesmentioning
confidence: 99%